Removals and Revisions of Cervical Total Disc Replacement Devices in a Consecutive Series of 1626 Patients Beginning With the First Case Experience in 2003 - Blumenthal, Scott L; Griffin, Cody; Courtois, Emily C; Guyer, Richard D; Zigler, Jack E; Shellock, Jessica L; Ohnmeiss, Donna D (Spine (Philadelphia, Pa. 1976), 2024)
Retrospective cohort study. The purpose of this study was to investigate the rate of cervical total disc replacement (TDR) device removal or revision. Cervical TDR has gained acceptance as an alternative to anterior cervical discectomy and fusion in appropriately selected patients. There have been concerns over device safety, one measure of which is subsequent surgery related to device problems. A consecutive series of 1626 patients undergoing cervical TDR from 2003 to June 2021 were included, consisting of TDRs up to 3 levels and hybrids (TDR and fusion). TDR removal or revision surgeries and reasons for these surgeries, procedures performed, and duration from index procedure were recorded. Data were analyzed to determine the removal/revision rate and factors possibly related to these events. There were 24 removals/revisions (1.48%) in the 1626 patients. Removal was performed in 23 cases (1.41%) and revision in 1 (0.06%). Among removal cases, anterior cervical discectomy and fusion was performed in 18 and TDR was replaced with another TDR in 5. Removals with fusion included 5 cases of osteolysis with/without Cutibacterium acnes , 4 device displacement/migration, 4 posterior spinal pathology, and one for each of the following: metal allergy, approach-related complications, malpositioning, subsidence, and hypermobility. The revision involved TDR repositioning 3 days after index surgery. There were 66 patients for whom a minimum of 10-year follow-up was confirmed, and none had removal/revision surgery 10 or more years after index surgery. There was no relationship between the occurrence of removal/revision and age, sex, body mass index, or physician experience (learning curve). The removal/revision rate was significantly higher in FDA trials versus postapproval (4.1% vs . 1.3%, P < 0.05). In this large consecutive series of patients, 1.48% of cervical TDRs were removed/revised. The low rate of removals/revisions over a long period of time provides support for the devices' safety. Level IV.